Personal medicines storage in New Zealand - Hewson C; Shen CC; Strachan C; Norris P (CSIRO Publishing, 2013)
INTRODUCTION: Poor storage of medicines can reduce their efficacy, yet little is known about how people store medicines in their homes and elsewhere, why these locations are chosen, and whether the conditions are suitable for medicines storage. AIM: To investigate where medicines are commonly stored in New Zealand households, why, and the typical conditions-temperature and relative humidity-in those places of storage. METHODS: Data from a large qualitative study on the meanings of medicines were analysed to explore where people store medicines in their households, and why. A data logger was used to log temperature and relative humidity in common medicine storage places, such as homes and cars. RESULTS: Kitchens and bathrooms were the most commonly reported storage places, with people influenced by convenience, desire to remember to take medicines, and child safety when deciding where to store medicines. High temperatures and humidity were found in kitchens and bathrooms, extreme temperatures in a car and a backpack, and extremely low temperatures in checked-in luggage on a plane. DISCUSSION: Temperature- and humidity-sensitive medicines should not be stored long-term in common storage locations, such as kitchens and bathrooms. Conditions in these places may not comply with the recommended storage conditions given by the manufacturer. Furthermore, medicines should not be left in backpacks or cars, especially if the vehicle is in the sun. Medicines that may degrade upon freezing and thawing - such as protein-containing medicines, emulsions, suspensions and some solutions - should not be stored in the cargo hold of a plane.